Epidemiology of self-medication in Ethiopia: a systematic review and meta-analysis of observational studies - Mekonnen Sisay; Getnet Mengistu; Dumessa Edessa (BMC, 2018)
Abstract Background Self-medication is the use of drugs to treat self-diagnosed disorders and/or symptoms, or the intermittent or continued use of a prescribed drug for recurrent disease or symptoms. This phenomenon is alarmingly increasing over time despite the occurrence of health-related hazards. This study is, therefore, aimed to quantitatively estimate self-medication practice and possible reasons for it in Ethiopia. Methods Data were identified from major databases and indexing services including EMBASE (Ovid), PubMed, MEDLINE (Ovid), and Google Scholar. Both published and unpublished records addressing self medication practice in Ethiopia without time limit were included for the study. Data were extracted with structured format prepared in Microsoft Excel and exported to OpenMeta[analyst] version 3.3 software for analyses. Pooled estimation of outcomes was performed with DerSimonian-Laird random-effects model at 95% confidence level. Sensitivity and subgroup analyses were also considered. Degree of heterogeneity of studies was presented with I2 statistics. Publication bias was also performed with the help of Comprehensive Meta-Analysis version-3 software and presented with funnel plots of standard error supplemented by Begg's and Egger's tests. The study protocol is registered on PROSPERO with reference number ID: CRD42018093790. Results A total of 27 studies with 9586 participants were included for the study. The pooled prevalence of self-medication in Ethiopia was found to be 44.0% (95% confidence interval [CI]: 35.1, 52.8). Geographical-based subgroup analysis revealed that the highest prevalence was observed at the capital of Ethiopia, Addis Ababa, 62.8% (95% CI: 42.3, 83.2). Population based analysis indicated that healthcare professionals and students were the main practitioners of self-medication. Besides, the prevalence of self-medication practice in pregnant women is approximately 22.9% (95% CI: 9.8, 36). The most common reasons to practice self-medication were previous experience of clients and/or familiarity of treatments, 31.3% (95% CI: 21.5, 41.1) and perceived mildness of the illness, 31.1% (95% CI: 26.0, 36.2). The pooled prevalence of analgesics, antimicrobial agents and gastrointestinal drugs were 46.1% (95% CI: 36.2, 56.1), 28.2% (95% CI: 19.6, 36.8), and 14.9% (95% CI: 7.8, 21.9), respectively. Conclusion Self-medication practice becomes a common phenomenon in Ethiopia. The use of prescription-only medications including antimicrobial agents without medical consult has become alarmingly high. This practice will come with potential health related hazards including emergence of antimicrobial resistance. Therefore, there must be a multitude of strategies for reversing the current worrying trends of self-medication.